Could serum Raftlin and GPER-1levels be new biomarkers for early detection of non-small cell lung cancer? - Aykut Eliçora; Berrak Güven; Hüseyin Engin; Gokcen Tugba Çevik; Hüseyin Fatih Sezer (Journal of Cardiothoracic Surgery)
Abstract Background Lung cancer is the leading cause of cancer-related deaths worldwide. Therefore, the search for new biomarkers continues in order to diagnose lung cancer at an early stage. In this study, we investigated blood levels of G-protein associated membrane estrogen receptor (GPER)-1 and Raftlin as markers of early-stage in lung cancer. Methods Lung cancer cases admitted to our hospital between 2016 and 2018 were included in our study. GPER-1 and Raftlin levels were measured by Enzyme-Linked Immunosorbent Assay (ELISA) in blood samples taken from patients diagnosed with lung cancer and healthy volunteers. Results There were 64 cases in total, 32 cases in lung cancer group and 32 cases in control group. We evluated GPER-1 levels for each group. GPER-1 level was 2.54 (IQR: 1.08–5.78) ng/mL in the lung cancer group and 5 (IQR: 2.69–7.99) ng/mL in the control group. ROC analysis value for GPER-1, (AUC) was 0.66 (p < 0.01). Raftlin levels were 4.5 (IQR: 3.3-11.52) ng/mL in control group and 7.77 (IQR: 6.24–9.85) ng/mL in lung cancer group. ROC analysis value for Raftlin, (AUC) was 0.629(P = 0.09). Conclusions In our study, there was no statistically significant difference between our groups in terms of Raftlin values. Therefore, it was thought that Raftlin could not be a specific marker in the diagnosis of lung cancer. GPER-1 was found to be lower in the lung cancer group than in healthy individuals. Therefore, it was thought that GPER-1 could be evaluated as a diagnostic marker in lung cancer. However, we think that more definitive results can be obtained by determining the tissue and expression level of GPER in lung cancer with further studies.